The Metaphor in William Shakespeare’s Poem:“Sonnet LXIII” - Noni Marlianingsih (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
This study uses stylistic focused on the theory of figure of speech. Stylistic approach is done by analyzing the entire poem and continued to interpret their characteristics, and to find out the whole meaning of poem. Technique of data analysis uses qualitative descriptive analysis. The descriptive data was taken from the form of phrases, words, and sentences in the Sonnet 73 poems by William Shakespeare. The main problem of this research was to find out the metaphor in sonnet 73. Metaphor is a figure of speech that makes a comparison describing one thing as another, suggesting a likeness between them. It does not use “like” or “as”. This poem talks about aging, dying, and death, and portrays a feeling from the poet when he is so close to death and it influences his love relationship with his dear friend.Key words: Metaphor, Poem, Sonnet, William Shakespeare.